2011
DOI: 10.1159/000334357
|View full text |Cite
|
Sign up to set email alerts
|

A New Vasculitis Activity Score for Predicting Death in Myeloperoxidase-Antineutrophil Cytoplasmic Antibody-Associated Vasculitis Patients

Abstract: Background/Aims: Myeloperoxidase-antineutrophil cytoplasmic antibody (MPO-ANCA)-positive microscopic polyangiitis patients with renal involvement have been shown to have a progressive clinical course. In this study, we compared the clinical utility of the Japanese Vasculitis Activity Score (JVAS) with the Birmingham Vasculitis Activity Score (BVAS) for predicting death in patients with MPO-ANCA-associated renal involvement. Methods: Sixty-nine patients with MPO-ANCA-associated vasculitis with renal involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This study demonstrates the importance of investigating for pulmonary manifestations of AAV in all patients, regardless of disease type or severity. While previous studies have focused on one particular condition within the spectrum of AAV , this study has shown that this is a significant problem even in those conditions which have not been classically associated with pulmonary involvement. The results demonstrate that such complications could be associated with an adverse effect on mortality.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This study demonstrates the importance of investigating for pulmonary manifestations of AAV in all patients, regardless of disease type or severity. While previous studies have focused on one particular condition within the spectrum of AAV , this study has shown that this is a significant problem even in those conditions which have not been classically associated with pulmonary involvement. The results demonstrate that such complications could be associated with an adverse effect on mortality.…”
Section: Discussionmentioning
confidence: 76%
“…This study goes further in that it has also incorporated patients with CSS and MPA, giving an overall idea of the effects of pulmonary involvement of AAV, rather than being limited to one condition. The effect of pulmonary vasculitis on mortality was also considered in a recent trial of a vasculitis activity score in patients with MPA . This study compared the Birmingham Vasculitis Activity Score (BVAS) with the Japanese Vasculitis Activity Score (JVAS) and found respiratory involvement to be a greater predictor of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall and ESRD-free survival rates significantly differed between grades I/II, III, and IV in this study even though some patients did not have renal involvement. A previous report also showed that score based on this system was a good predictor of mortality in patients with MPO-AAV [19]. As for the EUVAS-defined disease severity, severe disease was a good predictor of 6-month overall and ESRD-free survival, but the difference of these outcomes was not apparent among limited, early systemic, and generalized diseases.…”
Section: Discussionmentioning
confidence: 84%
“…Bakoush and coworkers followed 83 patients; neither survival nor ESKD was predicted by BVAS in their cohort, with less severe renal failure compared to our patients [ 9 ]. In Japanese patients with MPO-ANCA disease, no association was found between BVAS and mortality during the two years follow-up [ 20 ]. In another investigation there was no difference between the baseline BVAS of survivors and non-survivors; baseline BVAS did not, but BVAS at 1 and 3 months predicted survival [ 21 ].…”
Section: Discussionmentioning
confidence: 99%